Research on interleaved training for massive MIMO downlink with multi-user zero-forcing precoding - Cheng ZHANG; Minjie DING; Chang LIU; Jing Yindi; Fei YU; Yongming HUANG (Tongxin xuebao)
To solve the channel acquisition overhead problem of frequency division duplex massive MIMO, for the typical scenario of zero-forcing (ZF) precoding at the base station with users’ quality of service guarantee, a supervisory mechanism for the signal-to-interference-and-noise ratio (SINR) was introduced, and a multi-user antenna-by-antenna interleaved training scheme was designed.Then, considering the additional time overhead introduced by the interleaved training, a multi-user interleaved training scheme based on antenna grouping was designed.Closed-form expressions of the average training length, transmission success rate, and average effective sum spectrum efficiency were derived for the proposed schemes.Theoretical and simulation results reveal the impact of transmit power, SINR threshold, user number, group length, and the error level of channel on the performance of the proposed schemes, and demonstrate that the proposed schemes significantly reduce the pilot overhead and improve the transmission success rate compared to the full and partial training.